2021
DOI: 10.1186/s12887-021-02556-9
|View full text |Cite
|
Sign up to set email alerts
|

Gliosarcoma in patients under 20 years of age. A clinicopathologic study of 11 cases and detailed review of the literature

Abstract: Background Gliosarcoma is a rare variant of IDH- wild type glioblastoma with both glial and mesenchymal differentiation. It accounts for approximately 2% of glioblastomas and has a poor prognosis similar to that of classic glioblastoma. It is seen mostly between 40 and 60 years of age with a mean age over 50 years. Pediatric gliosarcoma is even rarer than gliosarcoma in adults. We describe the clinicopathological features of gliosarcoma in patients under 20 years of age and determine whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
8
0
3
Order By: Relevance
“…To the best of our knowledge, only 13 cases have been reported in the literature [10,11]. Although very few cases exhibited longer outcomes, infantile gliosarcomas share a gloomy prognosis with adult gliosarcomas [10,11]. Different from adults and children, infant-type gliomas do not show clear association of histologic tumor grade and clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To the best of our knowledge, only 13 cases have been reported in the literature [10,11]. Although very few cases exhibited longer outcomes, infantile gliosarcomas share a gloomy prognosis with adult gliosarcomas [10,11]. Different from adults and children, infant-type gliomas do not show clear association of histologic tumor grade and clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Infantile (<3 years old) gliosarcomas are extremely rare. To the best of our knowledge, only 13 cases have been reported in the literature [10, 11]. Although very few cases exhibited longer outcomes, infantile gliosarcomas share a gloomy prognosis with adult gliosarcomas [10, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Até o momento, mais de 63% dos casos analisados são Gliomas, afetando mais, frequentemente, o hemisfério direito, no lobo frontal. Na literatura não há nenhum artigo que traga a frequência quanto ao hemisfério e lobo como a aqui apresentada, porém, há evidências quanto a estruturas afetadas e, comumente, associadas a casos de câncer infantil 11,12 .…”
Section: Resultsunclassified
“…Ten deaths have been reported in the included literature, most of which were related to intraventricular hemorrhage or hemorrhage into the hypothalamus. Out of these 10 deaths, three cases were due to high-grade gliomas (glioblastoma and gliosarcoma) ( 11 , 24 , 35 ). On the other hand, van Baarsen and colleagues suggested that hemorrhage into glioma of the optic nerves carries a more benign course than hypothalamic and chiasmal ones since this type of hemorrhage is confined to the orbit and does not cause intracerebral damage ( 6 ).…”
Section: Discussionmentioning
confidence: 99%